2016
DOI: 10.4049/jimmunol.1600049
|View full text |Cite
|
Sign up to set email alerts
|

Type I and III IFNs Produced by Plasmacytoid Dendritic Cells in Response to a Member of theFlaviviridaeSuppress Cellular Immune Responses

Abstract: The pestivirus noncytopathic bovine viral diarrhea virus (BVDV) can suppress IFN production in the majority of cell types in vitro. However, IFN is detectable in serum during acute infection in vivo for ∼5–7 d, which correlates with a period of leucopoenia and immunosuppression. In this study, we demonstrate that a highly enriched population of bovine plasmacytoid dendritic cells (DCs) produced IFN in response to BVDV in vitro. We further show that the majority of the IFN produced in response to infection both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 70 publications
2
27
0
1
Order By: Relevance
“…As pDC of other species have repeatedly been described for their ability to rapidly produce large amounts of type I interferons [6], the cytokines that are essential for innate immune responses against viruses [87], we were surprised to find that bovine pDC only marginally upregulated IFN gene expression upon TLR stimulation. Most of the studies that have investigated bovine IFN responses have either detected mRNA for bovine type I IFN [88,89] or mRNA for ISGs [90,91] by quantitative RT‐PCR with total RNA samples from blood or tissues, or have looked at IFN activity by Mx‐CAT reporter assays [92‐96]. Two studies [92, 96] found type I IFN activity in cells that phenotypically resemble the current phenotypic definition of bovine pDC [14].…”
Section: Discussionmentioning
confidence: 99%
“…As pDC of other species have repeatedly been described for their ability to rapidly produce large amounts of type I interferons [6], the cytokines that are essential for innate immune responses against viruses [87], we were surprised to find that bovine pDC only marginally upregulated IFN gene expression upon TLR stimulation. Most of the studies that have investigated bovine IFN responses have either detected mRNA for bovine type I IFN [88,89] or mRNA for ISGs [90,91] by quantitative RT‐PCR with total RNA samples from blood or tissues, or have looked at IFN activity by Mx‐CAT reporter assays [92‐96]. Two studies [92, 96] found type I IFN activity in cells that phenotypically resemble the current phenotypic definition of bovine pDC [14].…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferon (IFN) is abundantly produced in virus-infected cells soon after infection, as well as a myriad additional virus-initiated modulatory effects, including induction of cellular inhibitors or repressors of transcription, and activation of IFN-I stimulated genes (ISG) and proteins, all in order to antagonize an antiviral host response [ 35 ]. Thus, IFNs have been used as antiviral agents in the treatment of several pathogens, including Flaviviridae [ 36 ]. Previous reports have shown that IFNα has activity against JEV in PK-15 cells [ 7 , 8 ] and BHK-21 cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, IFN-λ is transcribed and translated at higher rates than IFN-β in intestinal organoids [ 35 ]. Activation of an antiviral response in dendritic cells, in contrast, may stimulate production of both type I and III IFNs ( Figure 2 ) [ 37 , 41 , 42 ], which may act on a variety of cell types.…”
Section: Type I Versus Type Iii Interferonsmentioning
confidence: 99%